On the power of emotions. A semantic analysis of the expressions kogoś wryło, kogoś zamurowało and kogoś zatkało - Wołk, Mariola (Papers in Linguistics, 2019)
The paper focuses on three linguistic units: kogoś wryło, kogoś zamurowało and kogoś zatkało. These are one-argument predicates which encode results of intense emotions. They can be treated as lexical exponents of ‘surprise’ and similar concepts, although they differ from other expressions representing this category in, among other factors, their pragmatic value (as well as their vividness) and the intensity of the emotions that they convey. The paper describes the syntactic properties of the expressions and the mechanisms of predication (a specific shift from the concrete to the abstract, hyperbolisation), but most importantly it distinguishes elements of the semantic structure of the linguistic units. The ultimate aim of the presented characterization is an attempt to define the three examined expressions.